Woodchar as a sustainable reductant for ironmaking in the 21st century - Gupta R.C. (My University, 2025)
Presently, 850 million tons of steel is being produced in the world, mainly through the basic oxygen furnace (BOF) and electric arc furnace (EAF) route. The iron demand is met by hot metal produced in blast furnaces and smelting reduction units, whereas the cold metal is supplied as recycled scrap and sponge iron/HBI manufactured in DRI plants. This current practice uses fossil fuels (e.g., coke, coal, oil, and natural gas) as a source for chemical and thermal energy requirements and discharges CO2 as waste gas. This amounts to nearly 6% of the total CO2 discharge in the world. Due to mass awareness regarding global warming and its ill effects, the world has agreed to minimize CO2 emission, which was the main content of the KOYOTO Protocol signed in 1997. Motivated by the world opinion, efforts are being made to develop a renewable energy source for ironmaking to mitigate the effect of CO2. In this paper, the possibility of using woodchar as a reductant and energy source for ironmaking is explored in a scientific and rational way. The need for such an approach is explained in this paper. The basic principles of wood production are outlined with merits and limitations of its use. The woodchar preparation method is given before comparing the properties of woodchar with coke for use in ironmaking. The conceptual methods of ironmaking visualized for periods up to the years 2020, 2021-2040, and beyond 2041 are mentioned in brief. The paper concludes with a remark that intensive R & D may be needed to revive the use of woodchar in the future to mitigate global warming.